Do self-management interventions work in patients with heart failure?: an individual patient data meta-analysis - Jonkman, Nini H.; Peters-Klimm, Frank (Circulation, 2016)
Background—Self-management interventions are widely implemented in the care for patients with heart failure (HF). However, trials show inconsistent results, and whether specific patient groups respond differently is unknown. This individual patient data meta-analysis assessed the effectiveness of self-management interventions in patients with HF and whether subgroups of patients respond differently.Methods and Results—A systematic literature search identified randomized trials of self-management interventions. Data from 20 studies, representing 5624 patients, were included and analyzed with the use of mixed-effects models and Cox proportional-hazard models, including interaction terms. Self-management interventions reduced the risk of time to the combined end point of HF-related hospitalization or all-cause death (hazard ratio, 0.80; 95% confidence interval [CI], 0.71-0.89), time to HF-related hospitalization (hazard ratio, 0.80; 95% CI, 0.69-0.92), and improved 12-month HF-related quality of life (standardized mean difference, 0.15; 95% CI, 0.00-0.30). Subgroup analysis revealed a protective effect of self-management on the number of HF-related hospital days in patients <65 years of age (mean, 0.70 versus 5.35 days; interaction P=0.03). Patients without depression did not show an effect of self-management on survival (hazard ratio for all-cause mortality, 0.86; 95% CI, 0.69-1.06), whereas in patients with moderate/severe depression, self-management reduced survival (hazard ratio, 1.39; 95% CI, 1.06-1.83, interaction P=0.01).Conclusions—This study shows that self-management interventions had a beneficial effect on time to HF-related hospitalization or all-cause death and HF-related hospitalization alone and elicited a small increase in HF-related quality of life. The findings do not endorse limiting self-management interventions to subgroups of patients with HF, but increased mortality in depressed patients warrants caution in applying self-management strategies in these patients.